Evaluating willingness to contribute to a local public good: Application of contingent valuation to tsetse control in Ethiopia - Swallow, B.M.; Mulatu, W. (Elsevier, 1994)
African animal trypanosomiasis constaints the production of milk, meat and animal traction across much of sub-Saharan Africa. The tsetse-transmitted disease is particularly important in Ethiopia where at least six million cattle are exposed to the disease. In 1000 a trypanosomiasis control programme that used baited targets to kill tsetse flies was initiated in a case-study area in southwest Ethiopia. Major reduction in the density of tsetse flies and the prevalence of trypanosomiasis in cattle achieved during the first year were spoiled by the theft of a large number of the targets. It was postulated that part of the problem stemmed from a lack of local involvement. A survey of household heads was conducted to assess the prospects for greater local involvement. When asked what ought to be done to stop theft, respondents indicated their willingness to become more active in guarding the targets and detecting thieves. They also suggested roles for the research organization and local authorities. When asked contingent valuation questions about the maximum amounts of money and/or labour that they would be willing to contribute to the progrmme, 59 percent volunteered both money and labour and only 3 percent volunteered neither money nor labour. Willingness to contribute money was related to the gender of the household head, the number of cattle held by the house hold and the participation of the household in a monitoring exercise being conducted by the research organization. Willingness to contribute labour was related to employment status and the information available to the respondent about the programme. We conclude that contingent valuation, when integrated into a participatory research approach, can generate practical results for evaluating the prospects for local participation in the provision of local public goods.